VITAMIN D LEVEL AND ITS RELATIONSHIP WITH CYTOKINE LEVEL IN BRONCHO-OBSTRUCTIVE SYNDROME IN CHILDREN - Omonovna, Turayeva Nafisa; Azizovna, Khamzaeva Kamina (Research Focus International Scientific Journal, 2026)
The aim of the study was to investigate the effect of vitamin D on the course of broncho-obstructive syndrome in children and to determine its relationship with cytokine status. The study involved 86 patients aged 3 to 15 years with acute obstructive bronchitis, recurrent obstructive bronchitis and bronchial asthma. The patients underwent a single set of diagnostic studies: clinical examination, immunological examination, and a study of vitamin D levels in blood serum. The results of the study showed that vitamin D deficiency was accompanied by the development of secondary immune deficiency.